ШЎРО ҲОКИМИЯТИНИНГ БУХОРОДАГИ КУЧ ИШЛАТИШ ОРГАНЛАРИ ТАРИХИДАН (Scientific journal of the Fergana State University, 2023)
The article considers the history of the repressive policy of the force agencies of the Soviet government's in Bukhara, the revolutionary tribunals, ChK, the GPU in relation to the local population.